A: diff(int(sqrt(a+t),t,x,x^2))ans =2*x*(x^2 + a)^(1/2) - (a + x)^(1/2)
B: syms a t; diff(int(sqrt(a+t),t,x,x^2))ans =2*x*(x^2 + a)^(1/2) - (a + x)^(1/2)
C: diff('int(sqrt(a+t)','t',x,x^2))ans =2*x*(x^2 + a)^(1/2) - (a + x)^(1/2)
举一反三
- 17e0b849b7d64bd.jpg,计算[img=19x34]17e0ab14a855463.jpg[/img]实验命令为(). A: syms x;f=diff(asinsqrt(x))f=1/2/x^(1/2)/(1-x)^(1/2) B: f=diff(asin(sqrt(x)))f=1/2/x^(1/2)/(1-x)^(1/2) C: syms x;diff(asin(sqrt(x)))f=1/2/x^(1/2)/(1-x)^(1/2)
- 17da42840675a6d.jpg,计算[img=19x34]17da4275482315f.jpg[/img]实验命令为(). A: syms x;f=diff(asinsqrt(x))f=1/2/x^(1/2)/(1-x)^(1/2) B: f=diff(asin(sqrt(x)))f=1/2/x^(1/2)/(1-x)^(1/2) C: syms x;diff(asin(sqrt(x)))f=1/2/x^(1/2)/(1-x)^(1/2)
- 17e0b849d3a4a3b.jpg,计算[img=19x34]17e0ab14a855463.jpg[/img]的实验命令为( ). A: syms x; f=diff((1+sin(x)^2)/cos(x),1)f=2*sin(x) + (sin(x)*(sin(x)^2 + 1))/cos(x)^2 B: f=diff((1+sinx^2)/cosx,1)f=1/2/x^(1/2)/(1-x)^(1/2) C: syms x;f=diff((1+sinx^2)/cosx,1)f=2*sin(x) + (sin(x)*(sin(x)^2 + 1))/cos(x)^2
- 计算 [img=61x41]17da60e4003aded.png[/img]实验命令为(). A: syms x; limit(tan(x)/(2*x))ans =1/2 B: syms x; limit(tanx/(2*x))ans =1/2 C: limit(tanx/(2*x),x,0)ans =1/2
- 积分[img=136x52]1803d6afd4e6f95.png[/img]的计算程序和结果是 A: clearsyms xy=1/x^2/sqrt(x^2-1)int(y,x,-2,-1)3^(1/2)/2 B: clearsyms xint(1/x^2/sqrt(x^2-1),x,-2,-1)3^(1/2)/2 C: clearsyms xint(1/x/sqrt(x^2-1),x,-2,-1)-pi/3 D: clearsyms xint(1/x/sqrt(x^2-1),x,-2,-1)3^(1/2)/2 E: clearsyms xint(1/x^2*sqrt(x^2-1),x,-2,-1)log(3^(1/2) + 2) - 3^(1/2)/2
内容
- 0
函数\(y = {\left( {\arcsin x} \right)^2}\)的导数为( ). A: \(2\arcsin x{1 \over {\sqrt {1 - {x^2}} }}\) B: \( - 2\arcsin x{1 \over {\sqrt {1 - {x^2}} }}\) C: \(2\arcsin x{1 \over {\sqrt {1 + {x^2}} }}\) D: \( - 2\arcsin x{1 \over {\sqrt {1 + {x^2}} }}\)
- 1
已知“syms t; x=cos(t); y=sin(t); z=t; xt=diff(x,'t'); yt=diff(y,'t'); zt=diff(z,'t'); f=z^2/(x^2+y^2); g=sqrt(xt^2+yt^2+zt^2); I=int(f*g,t,0,2*pi)”,则下列说法正确的是【】
- 2
将[img=83x51]17de8a0fc777b0b.png[/img]表示为程序所能接受的表达式,正确的为 A: sqrt(pow(x, 2) / (pow(x, 2) + 1)) B: sqrt(pow(2, x) / (pow(2, x) + 1)) C: pow(sqrt(2, x) / (sqrt(2, x) + 1)) D: pow(sqrt(x, 2) / (sqrt(x, 2) + 1))
- 3
求函数$y = \root 3 \of {x + \sqrt x } $的导数$y' = $( ) A: ${{1 + 2\sqrt x } \over {\root 3 \of {{{\left( {x + \sqrt x } \right)}^2}} }}$ B: $ {{1 + 2\sqrt x } \over {6\root 3 \of {{{\left( {x + \sqrt x } \right)}^2}} }}$ C: $ {{1 + 2\sqrt x } \over {6\sqrt x \cdot \root 3 \of {{{\left( {x + \sqrt x } \right)}^2}} }}$ D: $ {{1 + 2\sqrt x } \over {\sqrt x \cdot \root 3 \of {{{\left( {x + \sqrt x } \right)}^2}} }}$
- 4
函数\(y = \arcsin x\)的导数为( ). A: \( - {1 \over {\sqrt {1 + {x^2}} }}\) B: \({1 \over {\sqrt {1 + {x^2}} }}\) C: \({1 \over {\sqrt {1 - {x^2}} }}\) D: \( - {1 \over {\sqrt {1 - {x^2}} }}\)